Association of visceral adiposity index with insulin resistance in adults with diabetes mellitus (IMC Journal of Medical Science, 2020)
Background and objectives: Visceral adiposity is linked to excess morbidity and mortality and positively correlates with the risk of insulin resistance, type-2 diabetes mellitus, cardiovascular disease and premature death. The study was conducted to find out the relationship between visceral adiposity index (VAI) and homeostatic model assessment insulin resistance (HOMA-IR) in diabetes mellitus (DM).Materials and methods: This cross sectional study was carried out on adult population with and without DM. Waist circumference (WC) and body mass index (BMI) were measured. BMI of 25-29.9 kg/m2 and ≥30 kg/m2 was defined as overweight and obese respectively. HOMA-IR method was used to calculate insulin resistance (IR). Standard formula using BMI, WC, triglyceride (TG) and high density lipoprotein cholesterol (HDL-c) was used to calculate VAI. Blood was analyzed for fasting blood glucose (FBS), TG, HDL-c and insulin level.Results: A total of 439 individuals were included in the study of which 269 had DM and 170 were healthy volunteers and the mean age was 41.47±6.82 and 36.16±7.44 years respectively. Compared to healthy controls, a greater number of diabetics had high VAI (86.5% vs. 98.9%) and high IR (43.5% vs. 85.1%). We found the highest sensitivity and specificity at a cut-off of 2.23 of VAI while at 3.65 had the highest specificity. Insulin resistance was observed significantly higher in those with diabetes compared to control, both in case of normal and high VAI at all cut-offs of VAI. Among anthropometric parameters (WC, BMI and VAI), VAI had positive (r=0.21, p